Preventive Maintenance of Boiler: A Case of Kuwait Industry - Ahmed S Kh R Q Alazemi; Mohammad Yeakub Ali; Mohd Radzi Che Daud (International Journal of Engineering Materials and Manufacture, 2019)
In Kuwait, industrial boilers are used extensively in food, chemical, oil and gas, textile, pharmaceutical, power plant sectors for generation steam. As a crucial item in industries, its maintenance is of utmost importance. As there are two main maintenance approaches such as reactive maintenance and preventive maintenance, the application of a typical maintenance is definitely based on types of application, safety concern, and cost benefit ratio. If a boiler is down for few days, it may cause huge loss as it interrupts subsequent steps especially in process industries. In this research, the importance of preventive maintenance strategy for steam boilers in Kuwaiti industries has been studied. Based on relative advantages and disadvantages, a proper strategy is proposed for better management and effective maintenance of boilers.